Pengaruh Pemahaman PMS (Penyakit Menular Seksual) pada Pelaut di Pelabuhan Tanjung Emas Semarang terhadap Kesehatan Reproduksi pada tahun 2013 - Mahsunah Etik; Nanang Indradi (Jurnal Maritim Polimarin, 2016)
A seaman is dealing with long distance relationship with main relatives especially spouse. On the other side of the normal human biological needs will certainly work normally anyway. Possibilities in order to deal with the biological desire, seafarer can only waiting petiently to go home to meet their partner or using sex aids. Various ways are also applied diverse. Some of them are loyal to the couple so they wait to go home to release desire, or perform a masturbation. They could also hire prostitutes. The various ways to release the passion could produced many effects, the most common is the impact of sexual health. Usually each individual understanding of literature related to PMS (Penyakit menular seksual) sexually transmitted disease STD, greatly affects the biological impingement. For those who know and understand the risk of STDs, preferred to conduct safe sex as faithful to their partner, or for those who like releasing desire with prostitute will use safety devices such as condoms. The conclusion of this research is the understanding of sexually transmitted diseases (STDs) to the seaman at Tanjung Emas in Semarang in 2013 has very positive influence.